The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1037/dhe0000313
|View full text |Cite
|
Sign up to set email alerts
|

Institutional pathfinders: Key lessons from program directors of AANAPISI grant-funded projects.

Abstract: Research on Asian American and Native American Pacific Islander Serving Institutions (AANAPISIs) has primarily focused on student-level experiences and outcomes. The current study shifts the gaze from the impact of programs on students to the execution of those programs by focusing on practitioners-program directors (PDs)-that manage the day-to-day operations of the AANAPISI grant-funded programs. We conducted interviews with five PDs to understand their role as an AANAPISI program director, the unanticipated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Scholarship on the experiences of AANAPISI practitioners are only beginning to emerge. Nguyen et al (2022) examined the experiences and roles of five AANAPISI program directors. They found that the role often extended beyond focusing on the students involved with the programs they directed.…”
Section: Aanapisi Practitioner Experiencesmentioning
confidence: 99%
“…Scholarship on the experiences of AANAPISI practitioners are only beginning to emerge. Nguyen et al (2022) examined the experiences and roles of five AANAPISI program directors. They found that the role often extended beyond focusing on the students involved with the programs they directed.…”
Section: Aanapisi Practitioner Experiencesmentioning
confidence: 99%